Heat transfer, erosion and acid condensation characteristics for novel H-type finned oval tube. Issue 1 (July 2015) - Wang, Y; Zhao, X; Tang, G
Abstract: Low efficiency of heat transfer, acid corrosion and erosion of economizers affect the economy and security in coal-fired power plants significantly. The H-type finned oval tube is proposed to alleviate these problems. Based on the H-type finned oval tube, we investigated three novel types of fins, including bleeding dimples, longitudinal vortex generators (LVGs), and compound dimple-LVG. We considered the three aspects together, and obtained the heat transfer, acid condensation rate and erosion loss. The results show that the tube bank with the new structured fins can improve the performance on the three aspects, and the compound dimple-LVG performs the highest comprehensive effect.